Perkembangan dan Tantangan Pasar Modal Indonesia - Rorizki, Fitri; Sakinah; Dalimunthe, Arpin; Silalahi, Purnama Ramadhani (As-Syirkah: Islamic Economic & Financial Journal, 2023)
The main indicator of economic health for any country is the capital market. Cities of Presence in Indonesia experience several ups and downs which can be seen from the fluctuating JCI indicator. As a result of globalization and economic integration, the work of currency exchange is very different from that of national, regional and international economics. Local investors are required to make a significant contribution to the Indonesian stock market to make it more resilient to various crises and dangers. With the rapid growth of Indonesia's youth population, there may be an opportunity that can be used to encourage people to refrain from active trading in the stock market. In addition, several other issues in the capital development market should be discussed, including the types of fixed price contracts transacted, policies to protect the rights of holders, the "game" involved in stock transactions, and a minimal level of understanding.